Repeatability and reliability of the diabetic foot self-care questionnaire in Arabic patients: A transcultural adaptation. - Navarro-Flores, Emmanuel María; Losa-Iglesias, Marta Elena; Becerro-de-Bengoa-Vallejo, Ricardo; Jiménez-Cebrián, Ana María; Rochdi, Loubna; Romero-Morales, Carlos; Palomo-López, Patricia; López-López, Daniel (Elsevier, 2022)
The diabetic foot self-care questionnaire is considered a self-care evaluation tool with 16 questions for assessing diabetic foot health disorders. To date, the DFSQ has been validated in different languages, but an Arabic version was lacking. Consequently, the purpose of this study was to translate and validate the Arabic version of the DFSQ (DFSQ-AR). Method: A suitable method was developed for the translation protocol and cross-cultural validation from Spanish to Arabic. Regarding the total marks from each sub-scale, agreement degrees and confidence were analyzed using Cronbach's α and intraclass correlation coefficient (ICC), respectively. In addition, the mean ± standard deviation differences between pre and post-tests were calculated and completed using Bland-Altman distribution plots. Results: Excellent agreement between the two versions was demonstrated based on Cronbach's α. Three subscales consisting of knowledge of foot hygiene, the appropriate use of footwear and socks, and podiatric self-care were added together to obtain the total score. Excellent retest reliability was shown for the total score. Test/ retest reliability was excellent for the self-care and shoe and socks sub-scales. There were no significant differences among any domains (p > 0.05). There were no statistically significant differences (P = 0.000) for the mean ± standard deviations (SD) between pre- and post-tests (98.09 ± 15.42) [93.75–102.43] and 97.96 ± 13.88 [94.5–101.86] points, respectively). Bland-Altman plots or clinically pertinent variations were not statistically significantly different. Conclusions: The DFSQ-AR is considered a strong and valid questionnaire with adequate repeatability in the Arabic language population.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/14144
Keywords: Pie diabético - Tratamiento; Cuidados de enfermería; Pie diabético; Cuestionario; Autocuidado; Autogestión